1983
DOI: 10.1161/01.cir.68.1.217
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative texture analysis in two-dimensional echocardiography: application to the diagnosis of experimental myocardial contusion.

Abstract: We postulated that the analysis of regional image texture in two-dimensional (2D) echocardiograms would be an accurate method to differentiate normal from abnormal myocardial structure. We tested this hypothesis with quantitative texture measures to study the regional, spatial distribution of echo amplitudes in 2D echocardiograms performed before and immediately after blunt left chest trauma was induced in six anesthetized dogs. After trauma the contused region of myocardium appeared brighter and exhibited an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
45
1

Year Published

1983
1983
2016
2016

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 124 publications
(47 citation statements)
references
References 25 publications
1
45
1
Order By: Relevance
“…The TA was used on echographic images to accurately identify ischemic and contused myocardium in animal models [10,11,15]. It has also been applied to identifying amyloid [14], hypertrophic cardiomyopathies [17], myocarditis [18] and myocardial ischemia [19] or viable myocardium [20].…”
Section: Data Acquisition and Image Digitizationmentioning
confidence: 99%
See 1 more Smart Citation
“…The TA was used on echographic images to accurately identify ischemic and contused myocardium in animal models [10,11,15]. It has also been applied to identifying amyloid [14], hypertrophic cardiomyopathies [17], myocarditis [18] and myocardial ischemia [19] or viable myocardium [20].…”
Section: Data Acquisition and Image Digitizationmentioning
confidence: 99%
“…Myocardial contusion is characterized on microscopical examination, by focal hemorrhages with hematoma formation, as well as myofibrillar fragmentation in the wall of the heart [10,11,12]. The interface between the area of normal and contused tissue due to the variation of the echo reflective which increase the brightness of the ultrasound reflection [10].…”
Section: Introduction Myocardial Contusion Descriptionmentioning
confidence: 99%
“…: mean, variance, frequency histogram) or textural measures (autocorrelation, cooccurrence matrices, run-length matrices, etc.) (46,47,55,57,(64)(65)(66)(67)(68)(69)(70)(71)(72)(73)(74). Lung tissue can be objectively evaluated using the attenuation of lung tissue, either as mean lung attenuation, or by measuring the attenuation of lung falling below a set value (the density mask) (46,47,55,57,73).…”
Section: Evaluation Of the Lung At Its Functional Interfacementioning
confidence: 99%
“…Several studies have pointed out that, despite a normal or supernormal conventional fractional shortening, the midwall left ventricular mechanic is impaired. 3,4 Moreover, a quantitative analysis of the 'texture' of the echocardiographic images, 5,6 represents a useful approach which allows the use of the ultrasound myocardial tissue characterisation (quantitative texture analysis) in this and in other 7 fields of interest. Previously our studies have shown that several myocardial textural videodensitometric parameters are impaired in essential hypertensive patients.…”
Section: Introductionmentioning
confidence: 99%